Purification and Characterisation of Endopeptidase Produced by Lactococcus Lactis Subsp. Lactis RI 11 - Woo, Kwan Kit (2001)
In the this study, 10 isolates of Lactic Acid Bacteria (LAB) were isolated from ikan rebus (steam fish) purchased from a local market, was characterised by phenotypical and biochemical characteristics. Eight isolates were identified as Lactococcus lactis subsp. lactis and were evaluated for endopeptidase activity. As the endopeptidase activity of the crude cell extracts varied among isolates, only Lc. lactis subsp. lactis RI 11 was selected for further study. The optimum endopeptidase activity was at pH 7.5 and 45°C. The crude enzyme preparation was purified to apparent homogeneity by ammonium sulphate fractionation, muon and cation exchange chromatography and gel filtration chromatography. The purification procedure has resulted 1.55% yield and 2.36 purification fold. As the purified endopeptidase has 3 optimum temperatures (10°C, 50°C and 90°C) and pH (3.5, 6.5 and 9.5), it was likely that the endopeptidase consist more than one isoenzymes. The molecular mass of purified endopeptidase was approximately 14.15 kDa estimated with Sodium dodecyl sulphate-polyacrylamide gel electrophoresis analysis. However, a lower molecular mass of 3.9 kDa was obtained from gel filtration chromatography. In terms of substrate specificity, the purified endopeptidase showed higher substrate affinity towards bradykinin with a K.m value of 0.029 mM, whilst, oxidised insulin B chain demonstrated the highest production rate with the Vmax value of 10.52.